Keadilan Restoratif sebagai Upaya Penguatan Sistem Penegakan Hukum Terhadap Pelaku Penyelundupan Pengungsi - Arjuna Al Ichsan Siregar; Muhammad Endriyo Susila; Indra Firmansyah (Jurnal Hukum IUS QUIA IUSTUM, 2022)
The purpose of the research is to analyze first, the criminal arrangement of the perpetrators of refugee smuggling and its implementation in Indonesia. Second, if a restorative justice approach can be an alternative in an effort to strengthen the criminalization process for perpetrators of refugee smugglers. This normative juridical research uses a statutory and conceptual approaches. The results of the study conclude that first, criminal arrangements for perpetrators of smuggling refugees in Indonesia are regulated in Article 120 of Law Number 6 of 2011 on Immigration (Immigration Law). The regulation is very simple and in its implementation creates obstacles for law enforcement officers, including the absence of special rules, the absence of differentiating the threat of criminal sanctions between perpetrators, and obstacles in regulating the threat of special minimum and maximum imprisonment sanctions which are considered to greatly limit the space for law enforcers in an effort to provide fair punishment for the perpetrators. Second, the restorative justice approach can be an alternative in an effort to strengthen the criminal justice process against perpetrators of refugee smugglers by integrating them into the criminal justice system. The process of meeting between perpetrators and victims as well as the community runs in parallel with the process in court and the results can be considered by the judge when they want to impose a sentence on each perpetrator of refugee smuggling. Key Words: Smuggling of refugees; law enforcement; restorative justice AbstrakTujuan penelitian untuk menganalisis pertama, pengaturan pemidanaan terhadap pelaku penyelundupan pengungsi dan pelaksanaannya di Indonesia. Kedua, pendekatan keadilan restoratif dapat menjadi sebuah alternatif dalam upaya memperkuat proses pemidanaan terhadap pelaku penyelundupan pengungsi. Penelitian yuridis normatif ini menggunakan pendekatan perundang-undangan dan konseptual. Hasil penelitian menyimpulkan, pertama, pengaturan pemidanaan terhadap pelaku penyelundupan pengungsi di Indonesia diatur dalam Pasal 120 Undang-Undang Nomor 6 Tahun 2011 tentang Keimigrasian (UU Keimigrasian). Pengaturan tersebut sangatlah sederhana dan dalam pelaksanaannya menimbulkan kendala bagi aparat penegak hukum, di antaranya ketiadaan aturan khusus, tidak adanya pembedaan ancaman sanksi pidana antarpelaku, dan kendala pengaturan ancaman sanksi penjara minimum khusus dan maksimum khusus yang dinilai sangat membatasi ruang gerak penegak hukum dalam upaya memberikan sanksi yang adil kepada para pelakunya. Kedua, pendekatan keadilan restoratif dapat menjadi sebuah alternatif dalam upaya memperkuat proses pemidanaan terhadap pelaku penyelundupan pengungsi dengan mengintegrasikannya dalam sistem peradilan pidana. Proses pertemuan antara pelaku dan korban serta masyarakat berjalan secara paralel dengan proses di pengadilan dan hasilnya dapat menjadi bahan pertimbangan hakim ketika hendak menjatuhkan pidana kepada setiap pelaku penyelundupan pengungsi. Kata-kata Kunci: Penyelundupan pengungsi; penegakan hukum; keadilan restoratif